Factors Influencing the Sustainability of MSME Businesses with Digital Literacy as Moderation Towards a Green Indonesia - Surjadi, Merna; Hakki, Tandry Whittleliang; Zulkifli, Nabila Felicita (Dinasti Publisher, 2024)
Economic growth focuses on sustainability and environmental awareness. This can be achieved if individuals or citizens consciously take responsibility for environmental issues. The number of Micro, Small and Medium Enterprises (MSMEs) is currently 65 million business actors who are able to contribute 60.5 percent to the gross domestic product (GDP). This study aims to analyze the influence of Accounting Information Systems, Management Control Systems, Green Intellectual Capital, and Green Organizational Culture on the Sustainability of MSME Businesses. Where in this study also makes Digital Literacy which is a supporting factor in addition to advances in information technology used as a moderating variable between the variables: Accounting Information Systems, Management Control Systems, Green Intellectual Capital, and Green Organizational Culture. This study uses primary data conducted by distributing questionnaires to Micro, Small and Medium Enterprises in several major cities in Indonesia such as the targets in this study are MSMEs in the cities of Jakarta, Denpasar, Bandung, Surabaya and Medan. Based on the research results, it shows that Accounting Information Systems, Management Control Systems, and Green Intellectual Capital have a significant effect on the sustainability of MSME Businesses, but Green Organizational Culture does not have a significant effect on the sustainability of MSME businesses. Then Digital Literacy strengthens the influence of Accounting Information Systems and Management Control Systems on the Sustainability of MSME Businesses, but digital literacy does not strengthen Green Organizational Culture and Green Intellectual Capital on the Sustainability of MSME Businesses.